Effective method to identify and verify the Dirac-like point through finite photonic crystals with triangular lattice. (30th May 2017) - Li, Z. F.; Dong, G. Y.; Yang, X. L.; Meng, X. F.; Bi, K.
Abstract: The precise location of the Dirac-like point of a finite photonic crystal array with a triangular lattice can be identified easily from the transmittance spectrum of any output interface with the characteristic of a sharp cusp embedded in the extremum spectrum near the Dirac-like point. The transmission properties of the finite triangular lattice photonic crystal arrays with square and hexagonal shapes have been investigated systematically to demonstrate that the transmittance at the Dirac-like point has a close relation with the output interface feature of the photonic crystal array and the output interfaces with the same feature will bring about the uniform transmission characteristics in different directions. These results provide us with a more accurate and convenient method to identify the Dirac-like point of a photonic crystal with different lattice structures, array sizes and shapes, and give guidelines for its use in experiments.